Written on the Body Narrative (Re)constructions of Violence(s) - Cenedese, Marta-Laura (Logos Verlag Berlin, 2023)
This volume explores the bodies that are subjects and objects of violence; bodies that, by simply being, narrate their traumatic experience. Contributors attune to the dialogic and hybrid relations that connect bodies and environments, and to the horizons of imaginative, future-worldbuilding possibilities that they open through acts of transmission, translation, and transfer. Refracting to something other than the body's own physicality - to multiple (multidirectional) networks - the chapters in this volume map and weave an ecosystem of interlacing bodies that are human, animal, vegetal, natural and technological; that are both singular and collective (i.e. a social body); that are situated in both the physical and virtual space; that are mythological and ephemeral; and that express naturecultural entanglements.